Effects of human activities on mountain forest in northern China during the middle Holocene. (15th July 2022) - Ren, Xiuxiu; Huang, Xiaozhong; Huang, Chong; Wang, Tao; Shen, Zhongwei; Zhang, Xiaosen; Ding, Guoqiang; Ayyamperumal, Ramamoorthy; Zhang, Jun; Chen, Xuemei
Abstract: China has a long history of civilization and agriculture, and its terrestrial ecosystems have long been subjected to anthropogenic impacts. However, we lack detailed knowledge of the nature and timing of human impacts on the development of vegetation ecosystems in the mountain region of northern China during the Holocene, especially during the middle and late Neolithic periods. In this study, we used pollen and charcoal data, combined with the biomization method, from a sediment core from Mayinghai Lake to reconstruct the Holocene vegetation history of a mountain region in northern China. Considering the relatively warm and wet climatic conditions indicated by independent paleoclimate reconstructions, we conclude that our results provide a record of human impacts on the natural landscapes of the study region since ∼4.8 ka (1 ka = 1000 cal yr BP), which are mainly indicated by a decrease in the coverage of temperate deciduous forest (based on biomization scores), higher sedimentary charcoal concentrations, and an increase in the number of archaeological sites, both in the vicinity of the study site and throughout the whole of northern China. Our results provide new insights into the role of humans in the ecological evolution of this mountainous region during the Holocene, and we suggest that the impact of prehistoric humans on vegetation succession was potentially significant, which needs to be considered when using pollen records for paleoclimatic reconstruction. Highlights: Intensified human activities caused forest degradation during 4.8–3.6 ka in the Mayinghai Lake area of northern China. Intensified human activity was one of the major drivers of vegetation dynamics in northern China since the late Neolithic period. Human impacts on vegetation may bias climatic reconstructions based on fossil pollen records.